Strengthening Land Law Reforms through Legal Pluralism in Indonesia: Memperkuat Reformasi Hukum Pertanahan melalui Pluralisme Hukum di Indonesia - Damanik, Pandapotan (Rechtsidee, 2023)
This study explores the urgent need for reforms in Indonesia's land law system, specifically focusing on incorporating legal pluralism into the national legal framework. Utilizing a normative legal research method, the study scrutinizes primary and secondary legal documents, including the 1945 Indonesian Constitution, the Basic Agrarian Law, and the Job Creation Law, while also incorporating insights from related literature. The main finding indicates that although the Basic Agrarian Law (UUPA) has attempted to blend principles of customary and religious law into the national land law framework, its implementation still exhibits signs of weak legal pluralism, where state law dominates. This research suggests that adopting legal pluralism as a foundational principle in the UUPA could serve as a catalyst for fostering greater harmony between state and non-state laws, encouraging the development of policies that are more accountable and responsive to local realities. This holds significant implications in promoting agrarian justice and sustainability in land management in Indonesia, offering vital insights for ongoing legal reform efforts. Highlights: Inadequate integration of customary and religious law principles in the existing Basic Agrarian Law (UUPA). The potential of legal pluralism as a foundation to foster greater harmony between state and non-state laws. The urgent need for responsive policies that align with local realities to promote agrarian justice and sustainable land management in Indonesia. Keywords: Legal Pluralism, Land Law Reform, Agrarian Justice, Policy Development, Indonesian Constitution